The challenges of internalizing religious moderation values amid the rise of socio-political polarization - Muhamad Najib Aulia Zaman; Muhammad Syakur; Joni; Muh. Baehaqi; Sumarjoko; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2026)
Religious-based socio-political polarization is one of the main challenges in strengthening social cohesion and religious life in post-reform Indonesia. The increasing politicization of religious identity in the lead-up to the 2024 elections demonstrates that religion serves not only as a source of moral values but also as an instrument of political mobilization that has the potential to threaten moderation and tolerance among religious communities. This study aims to analyze the relationship between socio-political polarization and the internalization of religious moderation in Indonesia, values in the context of a politically and ideologically fragmented society. Data were gathered from 25 participants—religious leaders, academics, civil society activists, and young voters from five provinces—through in-depth interviews, observations, and document analysis using a qualitative approach with a phenomenological design. With the aid of NVivo 14 software, thematic approaches were used to analyze the data. The findings show that while religious moderation is still symbolic and has not yet fully ingrained itself in society's social consciousness, religious polarization is strengthened by the use of social media as a platform for political identity fights. The participation of interfaith leaders, religious digital literacy, and intercultural education are important elements that promote moderation; algorithmic media bias and political fragmentation are important obstacles.